Preparation and Characterization of Agar Based Magnetic Nanocomposite for Potential Biomedical Applications - Shah, Nasrullah; Zaman, Tahir; Rehan, Touseef; Khan, Salman; Khan, Waliullah; Khan, Abbas; Ul-Islam, Mazhar (Current Pharmaceutical Design, 2019)
Purpose: The purpose of the present study was to make a biocompatible agar based composite material via incorporation of appropriate additives within the agar matrix for potential applications in drug delivery and biomedical fields. Methodology: Agar based composites were prepared by the incorporation of magnetic iron oxide nano particles, graphite and sodium aluminum as additives in different proportions within the agar matrix by a simple thermophysico- mechanical method. The as prepared agar based composites were then characterized by different techniques i.e. FTIR, SEM, TGA, XRD and EDX analyses. The FTIR peaks confirmed the presence of each component in the agar composite. SEM images showed the uniform distribution of each component in the agar composite. TGA study showed the thermal stability range of different composite sheets. XRD pattern revealed the crystallinity and EDX analysis confirmed the elemental composition of the prepared composites. The prepared agar based composites were evaluated for antimicrobial activities against three pathogenic bacterial strains Escherichia coli, Staphylococcus aureus and Klebsiella pneumonia and the result indicated efficient antimicrobial activities for all composites. Conclusion: From the overall study, it was concluded that due to the non-toxic nature, thermal stability and excellent antibacterial properties, the prepared agar based composites can receive potential biomedical applications.
Keywords: agar